2009
DOI: 10.1084/jem.20082835
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NK cell activity by IL-17 allows vaccinia virus to induce severe skin lesions in a mouse model of eczema vaccinatum

Abstract: Threats of bioterrorism have renewed efforts to better understand poxvirus pathogenesis and to develop a safer vaccine against smallpox. Individuals with atopic dermatitis are excluded from smallpox vaccination because of their propensity to develop eczema vaccinatum, a disseminated vaccinia virus (VACV) infection. To study the underlying mechanism of the vulnerability of atopic dermatitis patients to VACV infection, we developed a mouse model of eczema vaccinatum. Virus infection of eczematous skin induced se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 28 publications
(40 reference statements)
5
70
1
1
Order By: Relevance
“…One potential interpretation is that the pathogenic T cells can continue to proliferate, resulting in induction of colitis when the T cell number exceeds the capacity of the NK cells to suppress the T cells. A second possibility is based on the recent report that IL-17 inhibits NK cell-suppressive ability (36). It has been suggested that the increased IL-17 production from T cells that occurs when the severity of the colitis increases may affect NK cell function.…”
Section: Discussionmentioning
confidence: 99%
“…One potential interpretation is that the pathogenic T cells can continue to proliferate, resulting in induction of colitis when the T cell number exceeds the capacity of the NK cells to suppress the T cells. A second possibility is based on the recent report that IL-17 inhibits NK cell-suppressive ability (36). It has been suggested that the increased IL-17 production from T cells that occurs when the severity of the colitis increases may affect NK cell function.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus skin infections exacerbate skin disease in patients with AD and modify the host response to environmental allergens and viral pathogens (258,259). Recent studies suggest that host-pathogen interactions stemming from the production of S. aureus-derived virulence factors, such as superantigens and alpha-toxin, contribute greatly to the skin inflammation seen in AD (260,261).…”
Section: Superantigens In Atopic Dermatitismentioning
confidence: 99%
“…In light of these data suggesting that B6-lpr mice were better protected than B6 wild-type mice as early as day 2 after infection ( Fig. 2A to C, 3C and D, and 5C and D), and because other data suggested that the NK cell percentages and ␥␦ T-cell percentages were increased in B6-lpr mice infected with VACV as compared to B6 wild-type infected mice, uninfected B6-lpr and B6 mice were examined for differences in NK and ␥␦ ϩ T-cell numbers, as these lymphocytes are thought to exert effector functions early in VACV infections (6,28,35,51).…”
Section: Resultsmentioning
confidence: 98%
“…This enhanced resistance to infection was manifested as early as 2 days postinfection, when there was an elevation in the numbers of several different leukocyte populations previously shown to provide resistance to poxvirus infections: NK cells (6,12,28,35), ␥␦ ϩ T cells (51), and memory phenotype conventional ␣␤ T cells (3, 47, 52, 70). We suggest, therefore, that the heightened state of activation occurring in FAS pathway-mutant individuals might actually provide enhanced resistance to certain viral infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation